CHARACTERISTICS OF INDIVIDUAL AND ENTREPRENEURIAL BEHAVIOR OF OYSTER MUSHROOM FARMERS IN PAYAKUMBUH CITY - Revi Ernanda; Chika Sumbari; Fastabiqul Khairad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
This study aims to analyze individual factors and entrepreneurial behavior of oyster mushroom farmers in Payakumbuh. The entrepreneurial behavior characteristics of oyster mushroom farmers were analyzed descriptively from 60 selected farmers using a non-probability sampling technique, namely purposive sampling. The results showed that individual factors consisting of experience, self-confidence, motivation to try farming, skills, perceptions of effort, and desire to try were classified into the high category. Individual factor variables that have a high level of perception for farmers are high desire to try. Entrepreneurial behavior consisting of persistence in trying, responsiveness to opportunities, being innovative, daring to take risks, and being independent. Entrepreneurial behavior variables that have a high level of perception for farmers are diligent in trying, namely the farmer's persistence in pursuing farming and his patience in facing difficulties.